Microbial production of 2-pyrone-4, 6-dicarboxylic acid from lignin derivatives in an engineered Pseudomonas putida and its application for the synthesis of bio-based polyester. (May 2022) - Lee, Siseon; Jung, Ye Jean; Park, Si Jae; Ryu, Mi-Hee; Kim, Joo Eon; Song, Hye Min; Kang, Kyoung Hee; Song, Bong Keun; Sung, Bong Hyun; Kim, Yong Hwan; Kim, Hee Taek; Joo, Jeong Chan
Graphical abstract: Highlights: Lignin-derived monomers were successfully converted to PDC in Pseudomonas putida . A metabolically engineered host strain of P. putida increased PDC production. High titer and yield of PDC were obtained in optimized fed-batch fermentation. A novel polyester was synthesized using purified PDC, exhibiting thermal stability. Abstract: Lignin valorization depends on microbial upcycling of various aromatic compounds in the form of a complex mixture, including p -coumaric acid and ferulic acid. In this study, an engineered Pseudomonas putida strain utilizing lignin-derived monomeric compounds via biological funneling was developed to produce 2-pyrone-4, 6-dicarboxylic acid (PDC), which has been considered a promising building block for bioplastics. The biosynthetic pathway for PDC production was established by introducing the heterologous ligABC genes under the promoter P tac in a strain lacking pcaGH genes to accumulate a precursor of PDC, i.e., protocatechuic acid. Based on the culture optimization, fed-batch fermentation of the final strain resulted in 22.7 g/L PDC with a molar yield of 1.0 mol/mol and productivity of 0.21 g/L/h. Subsequent purification of PDC at high purity was successfully implemented, which was consequently applied for the novel polyester.